Synthesis and Antimicrobial Activity of New Thiazolidinone Derivatives With the use of γ-Ferrite Catalyst - S. P. Shrivastava; Nareshvarma Seelam; Rachana Rai (E-Journal of Chemistry)
A series of compounds were synthesized from 3,3'-(pyridine-2,6-diyl) bis (2-phenylthiazolidin-4-one(1), which was prepared from a one-pot three component condensation reaction of 2, 6-diamino pyridine, benzaldehyde and thioglycolic acid in the presence of γ-ferrite as a catalyst. The newly synthesized compounds were characterized by IR, 1HNMR, 13C NMR spectral data. All compounds were tested for anti bacterial and anti fungal activities.